Estrogen receptor positive breast cancers in BRCA1 mutation carriers: clinical risk factors and pathologic features - Tung, Nadine (BioMed Central, 2010)
INTRODUCTION: Most breast cancers that occur in women with germline BRCA1 mutations are estrogen receptor-negative (ER-) and also typically lack expression of progesterone receptor (PR) and HER2 overexpression. We undertook a study to assess the clinical factors that predict for an estrogen receptor positive (ER+) breast cancer in BRCA1 mutation carriers and to characterize the pathologic features of these tumors. METHODS: Clinical characteristics of BRCA1 carriers with 58 ER+ and 114 ER- first invasive breast cancers were compared. Pathologic features of BRCA1 ER+ cancers were compared to those of BRCA1 ER- cancers and to age-matched ER+ sporadic cancers. RESULTS: BRCA1 carriers aged ≥ 50 at diagnosis of first invasive breast cancer were more likely to have an ER+ cancer compared to those aged < 50 (57% vs 29%, P = 0.005). ER+ BRCA1 cancers were less likely than ER- BRCA1 cancers to have "BRCA-associated" features such as high mitotic activity, geographic necrosis/fibrotic focus, and pushing margins (RR 0.06, 0.22, 0.24; P < 0.001, 0.02, 0.03 respectively). When compared to sporadic ER+ cancers, ER+ BRCA1 cancers were more often of invasive ductal type (RR 2.4, P = 0.03), with a high mitotic rate (RR 5.0, P = 0.006) and absent or mild lymphocytic infiltrate (RR 10.2, P = 0.04). CONCLUSIONS: BRCA1 carriers who are older at first breast cancer diagnosis are more likely to have ER+ tumors than younger BRCA1 carriers. These ER+ cancers appear pathologically "intermediate" between ER- BRCA1 cancers and ER+ sporadic breast cancers raising the possibility that either some ER+ BRCA1 cancers are incidental or that there is a unique mechanism by which these cancers develop.